Understanding Pakistani Elementary School Teachers’ Attitudes toward Inclusive Education: Development of the Teacher Inclusion Attitude Questionnaire - Dr. Faisal Anis; Dr. Yasira Waqar; Dr. Yaar Muhammad (Indus Journal of Social Sciences, 2025)
The objective of the study was to develop an instrument, the Teacher Inclusion Attitude Questionnaire (TIAQ), for measuring Pakistani elementary school teachers’ attitudes towards inclusive education. There remains a dearth of contextually validated instruments to measure teacher preparedness in spite of Pakistan’s policy commitment towards inclusive education. TIAQ was developed by using extensive literature review and expert consultation in conjunction with aspects of culturally and contextually associated with the Pakistani education system. The researcher completed a questionnaire that was administered to 300 elementary school teachers drawn from public and private schools in Pakistan. The study investigated the underlying factor structure of teachers’ attitudes and preparedness for inclusion through principal axis factoring with varimax rotation. The analysis revealed a four-factor solution explaining 72.9% of the total Variance: Professional Knowledge and Preparedness accounted for 18.45%, Attitudes and Beliefs for 18.29%, Resource Availability and Support for 18.21%, and Collaboration and Professional Development for 17.95%. The sampling adequacy and suitability of the data for factor analysis were also confirmed by the Kaiser-Meyer-Olkin Measure (.891) and Bartlett’s test of sphericity (χ² = 4680.261, p < .001). High commonalities (ranging from .638 to .796) were shown for all items, with strong factor loadings (ranging from .778 to .880) on their respective dimensions. The psychometric properties of the TIAQ were found to be robust, and it was found to be a valid and reliable instrument for assessing teachers’ readiness for inclusion in the Pakistani context. The findings of these studies will help education stakeholders to have a validated tool to assess and enhance teacher preparedness to implement inclusive education practices in Pakistani elementary schools.